Clearing the fog: The grey zones of space governance - Jessica West; Jordan Miller (Centre for International Governance Innovation (CIGI), 2023)
Building on earlier research published by CIGI on the space-cyber nexus, the authors find that there is not one "grey zone" in space governance, but a cluster of nebulous governance challenges that are set to grow as our use of outer space not only expands but evolves in unexpected ways. The ultimate challenge, then, is to colour in governance frameworks so that less grey - less ambiguity - remains. In this paper, the authors peel back the layers of opacity that shroud the grey zone to reveal some of these unsettled governance issues that give rise to it, expand its scope and result in hidden harms. The analysis flows from the military concept of grey zone tactics to an identification of three entangled governance challenges. Stronger governance measures are needed, and the paper concludes by outlining opportunities for providing some colour in the grey zones of space governance by clarifying the parameters and rules of peaceful uses of outer space, making space activities and their potential harms more visible, and pursuing cross-domain governance discussions.
Keywords: 330